Witnessing the Revolutionary and Napoleonic Wars in German Central Europe - Leighton James (Palgrave, 2013)
This book explores the experience of the Revolutionary and Napoleonic Wars in German Central Europe. It examines both the experience of both combatants and civilians during a generation of warfare. Based on extensive archival research in Germany, Austria and Poland, the work combines an examination of the Alltagsgeschichte of the conflict with the consequences for identity construction. The work addresses the latest historiographical debates about the period as the first 'total war' and the changing nature of warfare in eighteenth and nineteenth century. The book contends that the war experience was, in general, marked by continuity rather than change. Despite literary changes in the eighteenth century and the ideological forces unleashed by the French Revolution, older interpretations of warfare continued to characterize the letters, diaries and memoirs of contemporaries.